The Marketing of Market-Based Value Creation in Today's Business Schools - Lorange, Peter (Senate Hall Academic Publishing, 2005)
This article argues for a new approach to the marketing of a business school’s value-propositions. Today’s modern business school is facing new demands for relevance and take-home value – from individuals and corporations alike. To meet this trend, a more proactive marketing of a school’s integrated services will be called for.To merely offer one’s traditional courses, say, via mass marketing, will thus no longer suffice. To deliver these new integrated value propositions, the very structural fabric of a business school may have to be modified. This, in turn, calls for the presence of a few fundamental conditions at the business school: A simple strategy, broad commitment to this, and faculty initiative – taking. And, the communication and marketing of it all will have to be revised. Substance, delivered in a “minimalistic” way, will be key for successful business school marketing in the future.
Keywords: marketing of business schools; structural changes in business schools; demands based on take-home value; minimalistic substancedriven marketing